Local Wisdom in Naming the Traditional Herbal Plants: A Semantic Analysis in Nias Language - Nazara, Benedicta Trisanta; Mendrofa, Denista Riska Cahyani; Harefa, Eldin Curtiel; Halawa, Dian Margaretha Enjelina (CV. Kalimasada Group Profesional, 2024)
This research investigates the local wisdom embedded in the naming of traditional herbal plants in the Nias language through a semantic analysis. The study addresses the gap in literature concerning the cultural and linguistic aspects of medicinal plant nomenclature in Nias, Indonesia. Utilizing a qualitative methodology, semi-structured interviews and documentation were conducted with five Nias individuals to gather insights on traditional herbal plants. Thirty traditional plant names were identified and analyzed for their semantic attributes. Findings reveal that the names often reflect physical characteristics, medicinal properties, or cultural significance, showcasing the rich botanical knowledge and cultural heritage of the Nias people. This study not only documents these unique plant names but also underscores the influence of local wisdom on the linguistic practices of the Nias community, highlighting the interplay between language, culture, and natural environment.